The Influence of the Zebra Mussel (Dreisena Polymorhpa) on Magnesium and Calcium Concentration in Water - Wojtal-Frankiewicz, Adrianna; Frankiewicz, Piotr (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2010)
In this study we examined changes in magnesium and calcium ion concentrations depending on Zebra Mussel biomass, pH values and temperature. We performed field experiments in years with different weather conditions using twelve 200 litre polycarbonate containers filled with 150 litres of non-filtered water from lowland, eutrophic reservoirs. Three treatments of the experiment were represented by: Phyto control with non-filtered water, Phyto+Dreis A with Zebra Mussel biomass of 500 g/m2, and Phyto+Dreis B with Zebra Mussel biomass of 1.000 g/m2. Magnesium and calcium ions concentrations were analyzed on an ion chromatograph (Dionex-1000). Results indicated a significant reduction in magnesium and calcium ion concentrations by Zebra Mussels (independent of mussel biomass), especially in the year with higher and more stable average temperatures. Mg concentration was significantly negatively correlated with temperature in this year. In both years of study the magnesium and calcium ion concentrations were negatively correlated with pH. Analyses of the Zebra Mussel’s impact on magnesium and calcium loss from water, linked with the influence of physical factors (temperature and pH), may be valuable for the management of invaded ecosystems.